Preoperative characteristucs of patients with improved quality of life one year fter coronary artery bypass surgery - C. J. Eales; T. D. Noakes; A. V. Stewart (AOSIS, 2003)
A study was conducted to determine the outcome of Coronary artery bypass graft (CABG) surgery in terms of patients' improved quality of life one year after the intervention. Quality of life was assessed in terms of return to work, absence of angina and increased activity. The analysis of the variables identified on admission between two groups (those who had an improved quality of life and those who did not have an improved quality of life) are presented. Patients with improved quality of life were married (p=0.02), men (p=0.01), with an income >R50,000 p/a (p=0.03), reported a normal sex-life prior to hospital admission (p=0.04), were taller (p=0.01), spent more hours at school participating in sporting activities (p=0.04) and had carried on with sport for more years prior to the surgery (p=0.01). There were no significant differences in weight or body mass index between the two groups.